Necrotizing enterocolitis: a potential protective role for intestinal alkaline phosphatase as lipopolysaccharide detoxifying enzyme - Martins, Raquel Dos Santos; Hulscher, Jan B. F.; Timmer, Albert; Kooi, Elisabeth M. W.; Poelstra, Klaas (Frontiers in Pediatrics, 2024)
Introduction: Necrotizing enterocolitis (NEC) is a life-threatening inflammatory disease. Its onset might be triggered by Toll-Like Receptor 4 (TLR4) activation via bacterial lipopolysaccharides (LPS). We hypothesize that a deficiency of intestinal alkaline phosphatase (IAP), an enzyme secreted by enterocytes that dephosphorylates LPS, may contribute to NEC development. Methods: In this prospective pilot study, we analyzed intestinal resection specimens from surgical NEC patients, and from patients undergoing Roux-Y reconstruction for hepatobiliary disease as controls. We assessed IAP activity via enzymatic stainings and assays and explored IAP and TLR4 co-localization through immunofluorescence. Results: The study population consisted of five NEC patients (two Bell's stage IIb and three-stage IIIb, median (IQR) gestational age 25 (24-28) weeks, postmenstrual age at diagnosis 28 (26-31) weeks) and 11 controls (unknown age). There was significantly lower IAP staining in NEC resection specimens (49 (41-50) U/g of protein) compared to controls (115 (76-144), P=0.03). LPS-dephosphorylating activity was also lower in NEC patients (0.06 (0-0.1)) than in controls (0.3 (0.2-0.5), P=0.003). Furthermore, we observed colocalization of IAP and TLR4 in NEC resection specimens. Conclusion: This study suggests a significantly lower IAP level in resection specimens of NEC patients compared to controls. This lower IAP activity suggests a potential role of IAP as a protective agent in the gut, which needs further confirmation in larger cohorts.